Management of Severe Spreading Odontogenic Infection in Third Trimester of Pregnancy: A Case Report - Ariestiana, Yossi Y.; Sylvyana, Melita; Tasman, Abel (Journal of Case Reports in Dental Medicine, 2020)
Objective: Odontogenic infections are the most prevalent disease worldwide that presenting initially as localized and could spread causing facial cellulitis and if not treated will develop into more serious facial spaces infections. Infections are common in pregnancy due to hormonal changes and altered immunological activity aggravating response to dental infection resulting in serious life threatening condition to the mother and to the foetus. The present paper reviews the emergency treatment in the third semester of pregnancy patient with spreading odontogenic infections.Method: A case report of 23-year old female with 28 weeks gestation admitted with toothache, right submandibular swelling, and severe trismus consistent with spreading of odontogenic infection into mandibular space. Her treatment included emergent incision and drainage of associated space, extraction of the offending teeth, and intravenous antibiotic coverage was explained. Mother and foetus were also assessed by the Obstetric and Gynaecology Unit.Result: Severe infection was successfully resolved. The patient condition improved and proceeded to a normal delivery with a healthy child.Conclusion: A third semester pregnancy patient with severe spreading odontogenic infection need a holistic and accurate emergency treatment by considering the foetal and maternal health and safety while following well established clinical guidelines in managing odontogenic infection